Age effects on traffic sign comprehension. (July 2020) - Schulz, Philipp; Labudda, Kirsten; Bertke, Volkmar; Bellgardt, Silvana; Boedeker, Sebastian; Spannhorst, Stefan; Kreisel, Stefan H.; Driessen, Martin; Beblo, Thomas; Toepper, Max
Abstract: Ageing is associated with changes in cognitive functions that affect fitness to drive. However, little is known about age effects on traffic sign comprehension (TSC). In this study, we assessed 37 older and 29 younger healthy drivers with a standardised traffic sign test and a comprehensive neuropsychological test battery. Older drivers showed lower TSC speed and tended to interpret more recent traffic signs less accurately than younger drivers. Higher cognitive functioning was generally associated with better TSC performances in both groups. In older drivers, TSC speed was related to specific cognitive functions such as cognitive flexibility and inhibition. Our findings suggest that traffic signs should appear in time to meet age-related constraints in TSC processing speed and should put low demands on inhibitory skills and cognitive flexibility. However, our findings also suggest that cognitive abilities are important for TSC regardless of age. In addition, a periodic update of traffic sign knowledge appears to be necessary. Highlights: Older drivers require more time for traffic sign comprehension (TSC). Age-related differences in TSC accuracy are limited to more recent signs. Traffic signs should put low demands on inhibitory skills and cognitive flexibility. For older drivers, traffic signs should appear in time. An update of traffic sign knowledge appears to be useful for all active drivers.